An efficient synthesis of 1,6-anhydro-N-acetylmuramic acid from N-acetylglucosamine - Calvert, Matthew B.; Mayer, Christoph; Titz, Alexander (Beilstein Journal of Organic Chemistry, 2017)
A novel synthesis of 1,6-anhydro-N-acetylmuramic acid is described, which proceeds in only five steps from the cheap starting material N-acetylglucosamine. This efficient synthesis should enable future studies into the importance of 1,6-anhydromuramic acid in bacterial cell wall recycling processes.
Keywords: N-acetylmuramic acid; anhydrosugars; antibiotic resistance; bacterial cell wall recycling; carbohydrate synthesis